Factors That Determine the Closure or Jeopardize the Continuity of a Micro and Small Enterprise - Aguilar Rascón, Oscar Cuauhtémoc; Velázquez, Rafael Posada (Organizations and Markets in Emerging Economies, 2019)
This paper explores the factors that determine the closure or jeopardize the continuity of micro and small enterprises (MSEs). We investigated the determinants of failure from the entrepreneur’s perspective using a qualitative approach, and five variables emerged. We discovered that there are internal and external variables that impact on an enterprise’s continuity, which are themselves correlated. We applied a formula to determine which variable had a higher weight, considering values ranging from 0 to 1, and the asymmetry is to the right. The instrument was applied to 35,571 MSEs, 26,720 of which were open and 8,851 were closed. 33,576 are Mexican and 1,995 Colombian enterprises.
Keywords: Developing MSEs; closing MSEs; MSEs